MHD MIXED CONVECTION IN A CHANNEL WITH A TRIANGULAR CAVITY - Rahman, M. M.; Öztop, Hakan Fehmi; Ahsan, A.; Kalam, M. A.; Billah, M. M. (Taylor & Francis Inc, 2012)
A numerical study has been carried out in an open channel, which have a heated triangular cavity at the bottom wall. The remaining walls of the channel are adiabatic. Flow inlets to the channel with uniform velocity and fully developed flow are accepted at the exit of the channel. Steady state mixed convection by laminar flow has been studied by numerically solving governing equations to obtain flow field and temperature distribution under the magnetic field and Joule effect. Equations are solved via the Galerkin weighted residual finite element technique. Calculations are performed for different governing parameters such as Hartmann number (10 <= Ha <= 100), Reynolds number (100 <= Re <= 2,000), Rayleigh number (10(3) <= Ra <= 10(5)), Joule parameter (0 <= J <= 5), and Prandtl number (1 <= Pr <= 10). It is found that heat transfer decreases with an increasing of the Hartmann number especially at higher values of Rayleigh number. Fluid temperature at the exit of the channel also decreases with increasing of Hartmann number. Fluid temperature at the outlet of the channel becomes higher at low Reynolds number and higher Rayleigh number. However, it decreases with the decreasing of the Reynolds number.
Keywords: Horizontal Bridgman Configuration; Constant Magnetic-Field; Buoyancy-Induced Flow; Numerical-Simulation; Heat-Transfer; Enclosure